Balanced Adjustable Mirrored Current Source with Common Mode Feedback and Output Measurement for Bioimpedance Applications - Klum, Michael; Schmidt, Malte; Klaproth, Joel; Pielmus, Alexandru-Gabriel; Tigges, Timo; Orglmeister, Reinhold (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2019)
Bioimpedance methods are used in a variety of applications such as impedance tomography, electrodermal activity detection and vascular disease assessment. Recent developments in portable and unobtrusive biosignal acquisition systems facilitate the integration of wearable bioimpedance applications including sleep monitoring, respiration estimation and fluid monitoring. However, the less stable measurement situation in a wearable scenario increases the requirements for the system's accuracy and adaptability. The current source of a bioimpedance system needs to drive large complex loads subject to vast variations over time while maintaining a high level of accuracy. The widely used improved Howland current source suffers from multiple disadvantages when considered for an adaptive bioimpedance system. We propose an optimized mirrored architecture which allows for a simple output current adjustment and current measurement without an additional shunt resistor in the load path. The system implements a common mode feedback system which includes balancing of the mirrored sources. Our design is validated by calculation, SPICE simulation and complex load measurements. We achieved output impedances in excess of 3 MΩ and derived a simplified transconductance function valid for frequencies up to 1 MHz. We conclude that the presented architecture is an important step forward towards accurate wearable bioimpedance acquisition. Employing generalized impedance converters, the output impedance could be further optimized.